Association of non-alcoholic fatty liver disease with microvascular complications of type 2 diabetes. Issue 6 (December 2019) - Afarideh, Mohsen; Aryan, Zahra; Ghajar, Alireza; Ganji, Morsaleh; Ghaemi, Fatemeh; Saadat, Mohammad; Heidari, Behnam; Mechanick, Jeffrey I.; Esteghamati, Alireza
Highlights: Association of NAFLD with diabetes-related microvascular complications was studied. NAFLD was inversely correlated with certain diabetes microvascular complications. Beneficial adaptations in sicker patients may contribute to this finding. Abstract: Introduction: Non-alcoholic fatty liver disease (NAFLD) affects risks of type 2 diabetes (T2D), diabetes-related complications, and cardiovascular disease in a complex manner. This study is designed to clarify associations of sonographically-detected NAFLD and serum liver enzymes with diabetes-related microvascular complications. Methods: A matched case-contorl study was designed for 440 patients with T2D and at least one of the chronic diabetes-related microvascular complications and 495 age- and gender-matched control patients with T2D. Results: Considering pre-existing and newly developed chronic microvascular complications, diabetic peripheral neuropathy was found in 347 out of 935 (37.1%) study patients, diabetic retinopathy in 141/935 (15.1%), and diabetic nephropathy in 103/935 (11.0%). Diagnosis of diabetic retinopathy and diabetic nephropathy were inversely associated with the presence of NAFLD in the crude logistic regressions (OR [95% CI] = 0.18 [0.05–0.63], p value = 0.007; OR [95% CI] = 0.17 [0.04–0.59], p value = 0.011, respectively). The subgroup of NAFLD with elevated liver enzymes had lower odds of having diabetic peripheral neuropathy in the fully adjusted model (OR [95% CI] = 0.34 [0.12–0.98], p value = 0.048). Conclusion: Diagnosis of NAFLD with or without elevated serum liver enzymes was inversely correlated with certain chronic diabetes microvascular complications. Possible explanations for this counter-intuitive and unexpected finding are discussed and center on reverse-causality, wherein sicker patients may develop beneficial compensatory physiological and behavioral adaptations. Diversity of studied patients, in particular with regards to the ethnic and racial differences among the Western and Asian populations may also partly account for contrasting findings of the relationship between NAFLD and microvascular complications of diabetes.